2018
DOI: 10.7150/jca.27611
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Anti-epidermal Growth Factor Receptor Monoclonal Antibodies in Nasopharyngeal Carcinoma: Literature-based Meta-analyses

Abstract: Background: Anti-epidermal growth factor receptor monoclonal antibodies (anti-EGFR mAbs), such as cetuximab and nimotuzumab have been used in the treatment of nasopharyngeal carcinoma (NPC), yet their efficacy and safety are undetermined.Materials and Methods: We performed two meta-analyses based on systematic searches of PubMed, EMBASE, the Cochrane Library and SinoMed: comparison 1 (standard therapy plus mAbs vs. standard therapy) and comparison 2 (radiotherapy plus concurrent mAbs vs. concurrent chemoradiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For patients with extremely high levels of EGFR, in whom the metastasis cannot be imaged, more active systemic treatments or preventive treatments should be considered. A recent meta-analysis demonstrated that anti-EGFR monoclonal antibody treatment combined with radiotherapy or chemoradiotherapy significantly improved OS and DFS in NPC patients ( 44 ) with tolerable side effects. This suggests that locoregionally advanced NPC would likely benefit from anti-EGFR monoclonal antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with extremely high levels of EGFR, in whom the metastasis cannot be imaged, more active systemic treatments or preventive treatments should be considered. A recent meta-analysis demonstrated that anti-EGFR monoclonal antibody treatment combined with radiotherapy or chemoradiotherapy significantly improved OS and DFS in NPC patients ( 44 ) with tolerable side effects. This suggests that locoregionally advanced NPC would likely benefit from anti-EGFR monoclonal antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It would be plausible that disrupting the interactions might break the balance of TME and thus cure the tumour. Besides the promising results of PD-1/PD-L1 blockade immunotherapy in NPC, antibodies targeting EGFR have been reported to enhance the current treatment paradigms for locoregionally advanced NPC 64 . We suspect that immune-suppressive interaction of CD200-CD200R1 and LGALS9-HAVCR2 among LAMP3 + DCs, Treg cells, and exhausted CD8 + T cells might be also potential immunotherapeutic targets for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clear consensus, most studies suggest that anti-EGFR monoclonal antibodies, especially nimotuzumab and cetuximab, confer significant benefits in patients with LA-NPC. According to a meta-analysis, addition of anti-EGFR monoclonal antibodies to standard therapy for NPC significantly improved OS (HR, 0.51; 95% CI, 0.39-0.66) compared to standard therapy alone [25]. In a case-control study based on intelligence platform, concurrent administration of nimotuzumab/ cetuximab with IC was found to be more effective, with a significant improvement in 3-year disease-free survival rate (84.3% vs. 74.3% P = 0.027) [9].…”
Section: Cost-effectiveness Analysis and Sensitivity Analysismentioning
confidence: 99%